Clinically relevant differences between assays for von Willebrand factor activity. (20th November 2018) - Boender, J.; Eikenboom, J.; van der Bom, J. G.; Meijer, K.; de Meris, J.; Fijnvandraat, K.; Cnossen, M. H.; Laros‐van Gorkom, B. A. P.; van Heerde, W. L.; Mauser‐Bunschoten, E. P.; de Maat, M. P. M.; Leebeek, F. W. G.; et al.
Abstract : Essentials It is unclear whether there are differences between von Willebrand factor (VWF) activity assays. We compared the four most used VWF activity assays in 661 von Willebrand disease (VWD) patients. All assays correlated excellently, but a discrepant classification was seen in 20% of patients. Differences between VWF activity assays have a large impact on the classification of VWD. Summary: Background: Measuring the ability of von Willebrand factor (VWF) to bind to platelets is crucial for the diagnosis and classification of von Willebrand disease (VWD). Several assays that measure this VWF activity using different principles are available, but the clinical relevance of different assay principles is unclear. Objective: To compare the four most widely used VWF activity assays in a large VWD patient population. Methods: We measured VWF:RCo (ristocetin to activate VWF + whole platelets), VWF:GPIbR (ristocetin + platelet glycoprotein Ib receptor [GPIb] fragments), VWF:GPIbM (gain‐of‐function GPIb fragments that bind VWF spontaneously without ristocetin) and VWF:Ab (monoclonal antibody directed against the GPIb binding epitope of VWF to mimic platelets) in 661 VWD patients from the nationwide 'Willebrand in the Netherlands' (WiN) Study. Results: All assays correlated excellently (Pearson r  > 0.9), but discrepant results led to a different classification for up to one‐fifth of VWD patients. VWF:RCo was not sensitive enough to classify 18% of patients and misclassified half of genotypic 2B VWD patients, especially those with p.Arg1306Trp. VWF:GPIbR was more sensitive, accurately classified the vast majority of patients, and was unaffected by the p.Asp1472His variant that causes artificially low VWF:RCo. VWF:GPIbM was the most precise assay but misclassified over a quarter of genotypic 2A, 2B and 3 patients. VWF:Ab, often not considered an actual VWF activity assay, performed at least equally to the other assays with regard to accurate VWD classification. Conclusion: Although the different VWF activity assays are often considered similar, differences between assays have a large impact on the classification of VWD.